A database of West European headwater macroinvertebrate stoichiometric traits. Issue 1 (7th October 2021) - Beck, Miriam; Billoir, Elise; Felten, Vincent; Meyer, Albin; Usseglio‐Polatera, Philippe; Danger, Michael
Abstract: Motivation: Ecological stoichiometry investigates the equilibrium and the fluxes of chemical elements and energy between organisms and their environment. Several studies have pointed out the value of integrating stoichiometric traits for a better understanding of the mechanisms behind community and ecosystem processes. Especially in the light of globally changing nutrient levels in freshwater systems, the link between stoichiometric traits and nutrient cycling or trophic interactions can improve our investigations of a species' or community's response to these changes. Benthic macroinvertebrate assemblages are widely used for biomonitoring in freshwaters, providing a large number of datasets gathering information about their taxonomic diversity at many different spatial and temporal scales. Likewise, an increasing number of large databases gives ready access to information on a variety of macroinvertebrate biological traits. The addition of stoichiometric traits to this pool of available information could thus expand the application of trait approaches and facilitate the study of the links between nutrient cycling and ecosystem functioning. Main types of variables contained: The database contains information on the elemental contents of 188 taxa, in terms of the major nutrients %C, %N and %P and the corresponding molar ratios C:N, C:P and N:P. We provide calculated taxon mean values as well as the underlying raw data at the individual level that were obtained from field sampling, supplemented by a literature search ( n  = 1, 555; 174 taxa). Major taxa and level of measurements: The database contains information on 188 macroinvertebrate taxa, available at species ( n  = 33), genus (96), tribe (9), subfamily (6), family (42), order (1) or class (1) levels. Software format: .csv file.